Dynamics parameters identification of rigid-body manipulators through natural oscillation - Jamisola, Rodrigo Jr. S. (Philippine computing journal)
This work will present an experimental procedure in identifying the moments of inertia, mass, and center of mass of a rigid-body manipulator through natural oscillations. Based on the response of the manipulator, the values of the dynamics parameters to be identified are adjusted in such a way that the desired natural oscillation is achieved. The experiments to be performed on a manipulator under torque control are composed of two sets: mass and center of mass identification. and moments of inertia identification. The first set of experiments will use an open-loop control, such that the natural oscillation is minimized. The second set of experiments will use a proportional control, such that the square of the natural oscillation is equal to the proportional gain. Thus each set of experiments has a well.defined objective function such that it can be treated as an optimization computation. The correct dynamics parameters are identified when the desired objective function is achieved. The proposed dynamics identification method is analyzed and a theorem is presented to support the claims presented in this work, together with simulation result.